Anti-N-methyl-D-aspartate receptor encephalitis associated with acute Toxoplasma gondii infection: A case report. Issue 7 (February 2018) - Cai, Xiaotang; Zhou, Hui; Xie, Yongmei; Yu, Dan; Wang, Zhiling; Ren, Haitao
Abstract: Rationale: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis has been recognized as the most frequent autoimmune encephalitis in children. Several infectious agents have been implicated in anti-NMDA encephalitis. Patient concerns: A previously healthy immunocompetent 9-year-old girl first presented with seizures, headaches and vomiting. Cerebrospinal fluid and brain magnetic resonance imaging were normal. After one week onset, the patient gradually developed unexplained personality and behavior changes, accompanied by fever and seizures again. Repeated CSF analysis revealed a slightly lymphocytic predominant pleocytosis and positive anti-NMDAR antibody. A variety of pathogenic examinations were negative, except for positive toxoplasma IgM and IgG. Diagnoses: The patient was diagnoses for anti-NMDA encephalitis associated with acute acquired toxoplasma gondii infection. Interventions: The patient received 10 days azithromycin for treatment of acquired toxoplasma infection. The parents refuse immunotherapy because substantial recovery from clinical symptoms. Outcomes: The patient was substantially recovered with residual mild agitation after therapy for acquired toxoplasma gondii infection. Two months later, the patient was completely devoid of symptoms, and the levels of serum IgM and IgG of toxoplasma gondii were decreased. Lessons: Acquired toxoplasma gondii infection may trigger anti-NMDAR encephalitis in children, which has not been reported previously. Clinicians should assess the possibility of toxoplasma gondii infection when evaluating a patient with anti-NMDA encephalitis.